Case Report: An extremely rare case of double extralobar pulmonary sequestration with anomalous supplying arteries originating from the abdominal aorta in the left thoracic cavity - Lv, Longfei; Zhai, Yunpeng; Zhao, Huashan; Guo, Rui; Xu, Hongxiu; Zhang, Shisong (Frontiers in Pediatrics, 2022)
To the best of our knowledge, double or multiple extralobar pulmonary sequestration (PS) with anomalous supplying arteries in the ipsilateral thoracic cavity has rarely before been reported. PS can be divided into two types: intralobar sequestration (ILS) and extralobar sequestration (ELS). We encountered a 5-month-old infant with double ELS in the left thoracic cavity that was incidentally detected during thoracoscopic surgery. Surgical exploration revealed two separate, well-circumscribed abnormal masses in the left thoracic cavity, and the patient was successfully treated using thoracoscopic surgery. Postoperative pathology confirmed that both masses were PS tissues. Accurate preoperative diagnosis using computed tomography (CT) alone may be inadequate in this type of case. Therefore, thoracoscopy may be more suitable for diagnosing and treating unusual ELS.